Wavelet analysis of the first pulse of initial breakdown process in lightning discharges - Mohd Esa, Mona Riza; Ahmad, Mohd Riduan; Cooray, Vernon (2013)
The investigation is done using wavelet transformation in order to seek for differences in the initial breakdown process between negative cloud-to-ground flash (CG), positive CG, cloud flash (IC), and isolated breakdown (IB) process. A total of 66 waveforms were selected from the collection of 885 waveforms collected during summer thunderstorm between May and August 2010 at the premise of Uppsala University, Uppsala, Sweden. The recording unit consisted of a flat plate fast electric field broadband antenna measuring system with the sampling rate set to 20 Megasamples per second. The analysis was conducted only on the first pulse for each lightning events and the output from the wavelet transformation is shown as normalized power spectrum plotted in time-frequency domain as shown in Figure 1 below. The first pulses in negative CG are found to radiate intensely in average frequency range between 186 and 1637 kHz. The energy radiated by the first pulses of positive CG mainly concentrated in the average frequency range between 57 and 599 kHz. As for the cloud flash, the first pulses found to be spread out in the average frequency range between 398 and 3656 kHz and for isolated breakdown, the energy spread out between 44 and 279 kHz. The positive CG and IB flashes are tending to radiate at lower frequencies range within smaller range when compared to negative CG and IC. IB has the smallest average frequency range at 235 kHz while the average frequency range of IC and negative CG are more than 10 times and 6 times larger than IB, respectively. It can be speculated that the initial breakdown process of positive CG and IB flashes are most likely initiated from the same discharge process in the thundercloud. On the other hand, the initial breakdown process of negative CG and IC are most likely initiated from different discharge processes.